Evolución de la brecha salarial de género en Colombia: Un análisis desde sus factores y políticas públicas 2010 - 2018 (2021)
The main objective of this document is to analyze the evolution of the gender pay gap in Colombia based on the factors affecting it, and the public policies implemented since the National Development Plans for the period 2010 – 2018. Work is being carried out to establish whether implemented public policies had a positive impact on the reduction of the wage gap and its factors, for which, in the process, the most representative factors affecting the pay gap were identified according to the methodology of the International Labour Organization (ILO), and exposed to the situation of women in the labour market , the National Development Plans for this period were subsequently identified and from there it was established that public policies were proposed around the reduction of the wage gap and its factors.